2013
DOI: 10.1155/2013/708659
|View full text |Cite
|
Sign up to set email alerts
|

Immunology and Oxidative Stress in Multiple Sclerosis: Clinical and Basic Approach

Abstract: Multiple sclerosis (MS) exhibits many of the hallmarks of an inflammatory autoimmune disorder including breakdown of the blood-brain barrier (BBB), the recruitment of lymphocytes, microglia, and macrophages to lesion sites, the presence of multiple lesions, generally being more pronounced in the brain stem and spinal cord, the predominantly perivascular location of lesions, the temporal maturation of lesions from inflammation through demyelination, to gliosis and partial remyelination, and the presence of immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 122 publications
1
125
0
2
Order By: Relevance
“…The oxidation-reduction thus triggered (redox cycling) precisely lead to the formation of ROS, such as the hydroxyl radical is particularly active in the initiation of lipid peroxidation. Similar phenomena of redox cycling seem to participate in the pathogenesis of hitting in MS [18]. Moreover, complex interactions, in degenerative processes, involve also glutathione, the NO and dopamine, which have the same ability to catalyze reactions of redox cycling of iron and copper.…”
Section: Discussionmentioning
confidence: 92%
“…The oxidation-reduction thus triggered (redox cycling) precisely lead to the formation of ROS, such as the hydroxyl radical is particularly active in the initiation of lipid peroxidation. Similar phenomena of redox cycling seem to participate in the pathogenesis of hitting in MS [18]. Moreover, complex interactions, in degenerative processes, involve also glutathione, the NO and dopamine, which have the same ability to catalyze reactions of redox cycling of iron and copper.…”
Section: Discussionmentioning
confidence: 92%
“…An alternative hypothesis proposes that MS is a neurodegenerative process exacerbated by sustained inflammatory activity (5). Being considered upstream to the primary activation of these disturbances, NF-κB is recognized as a proinflammatory cytokine response element located at the forefront of such impairment, according to its role into inflammatory pathways, controlling the activation, proliferation, and cytokine release following immune response, including (but not limited to) the focal inflammatory demyelinating lesions that, in MS, are characterized by perivascular infiltrates containing monocytes, a significant number of macrophages, and both T and B cells (6).…”
Section: The Nuclear Factor κB (Nf-κb) Pathwaymentioning
confidence: 99%
“…These sequential events may describe the initial stages of MS occurrence, suggesting a mechanism by which crosstalk between the circulation and the brain can lead to disruption of the BBB. It has been shown that oxidative stress significantly increases the production and function of matrix metallopeptidase (MMP)-2 and -9 in endothelial cells and macrophages (Yazdani et al 2011;Ortiz et al 2013;Mirshafiey et al 2014). The increased levels of these enzymes have been reported in astrocytes in MS lesions (Cuzner et al 1996).…”
Section: Multiple Sclerosismentioning
confidence: 99%